The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2169/internalmedicine.54.4942
|View full text |Cite
|
Sign up to set email alerts
|

Use of Rivaroxaban for the Effective Management of Disseminated Intravascular Coagulation Associated with Abdominal Aortic Aneurysm

Abstract: A 67-year-old man with non-valvular atrial fibrillation (AF) and previous myocardial and cerebral infarctions had uncontrollable bleeding after undergoing dental extraction because of an exacerbation of chronic disseminated intravascular coagulation (DIC) due to an abdominal aortic aneurysm. After successful treatment of the bleeding with the transfusion of fresh frozen plasma and platelets, nafamostat mesilate was used to treat the chronic DIC. Finally, rivaroxaban (an oral direct Factor Xa inhibitor) was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Accordingly, Xa inhibitor has recently been suggested as an alternative to subcutaneous heparin administration for aortic DIC if renal function is retained (17-19). TEVAR is a radical way of curing the symptoms of DIC (20) and also reduces the aortic-specific mortality in the chronic phase (21).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Xa inhibitor has recently been suggested as an alternative to subcutaneous heparin administration for aortic DIC if renal function is retained (17-19). TEVAR is a radical way of curing the symptoms of DIC (20) and also reduces the aortic-specific mortality in the chronic phase (21).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic DIC associated with aortic aneurysm/dissection is a primary cause of hemorrhagic diathesis in elderly patients. In aortic aneurysms, endothelial disruption associated with either dissection or atheromatous plaque rupture leads to the exposure of collagen and tissue factor, triggering the coagulation cascade, including the activation of FX, and leading to excess consumption of clotting factors and the induction of DIC [13]. Similarly, in aortic dissection, chronic expansion of the false lumen activates extrinsic tissue factors and intrinsic coagulation factors, leading to the exposure of subendothelial collagen tissue and the pooling of a high volume of blood in the false lumen.…”
Section: Discussionmentioning
confidence: 99%
“…We were the first to report that rivaroxaban - an oral activated factor X inhibitor - was effective for the treatment of DIC associated with aortic aneurysms ( 5 ). Subsequently, other authors have reported that rivaroxaban is effective for treating DIC associated with abdominal aortic aneurysms ( 15 ). Based on our earlier experience, in which a patient was treated with rivaroxaban (after we obtained approval from our hospital's medical ethics committee and after obtaining informed consent), following confirmatory reports from others, and after verifying that the PT-INR had been corrected following the discontinuation of warfarin, we initiated treatment with rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%